A China–New Zealand comparison of forgiveness. Issue 4 (2nd September 2013) - Hook, Joshua N.; Worthington, Everett L.; Davis, Don E.; Watkins, David; Hui, Eadaoin; Luo, Wenshu; Fu, Hong; Shulruf, Boaz; Morris, Paul; Reyna, Samuel H.
Abstract : The present study examined the practice of forgiveness among participants from China ( N  = 172) and New Zealand ( N  = 91). We tested a theoretical model describing the relationships between collectivism, individualism, and forgiveness. Participants from China were more collectivistic and less individualistic than were participants from New Zealand. Overall, participants from New Zealand were more forgiving than were participants from China. Collectivism was positively related to decisional forgiveness in Chinese participants. Decisional forgiveness independently predicted conciliatory behaviour among participants from China, but this was not the case for participants from New Zealand. Thus, the hypothesized model received qualified support.